Integration of Artificial Intelligence and Chatbots in Indonesian Language Learning: Enhancing the Writing Skills of Upper Elementary School Students - Fitri Andini; Nadila Putri Nassel; Afifah Rahmadani; Nuratna Fitri Hasanah; Annisya Azzahra; Atika Mawaddah; Putri Amalia Peza; Sintia Ayu Lestari; Dinia Putri Marsha; Putri Hana Pebriana (The Future of Education Journal, 2026)
The rapid development of digital technology, particularly Artificial Intelligence (AI), has brought significant changes to the field of education. One of the emerging innovations in learning is AI-powered chatbots, which provide interactive support to students throughout the learning process. This study aims to examine the integration of AI and chatbots in Indonesian language learning and their impact on improving the writing skills of upper elementary school students. The study employed a library research approach by analyzing relevant scholarly literature on the use of AI, educational chatbots, and writing instruction in elementary education. The findings indicate that AI and chatbot technologies can assist students in generating writing ideas, expanding vocabulary, improving grammar and spelling, and enhancing motivation to write. In addition, chatbots enable students to receive immediate and personalized feedback, making the learning process more effective and engaging. Nevertheless, the implementation of AI in education still requires teacher guidance to ensure that the technology is used wisely, critically, and in alignment with instructional objectives. Therefore, the integration of AI and chatbots has considerable potential as an innovative instructional approach to improving the writing skills of upper elementary school students in the digital era.